Pengelolaan Media Sosial Official dengan Pendekatan Jurnalisme Kontemporer di Desa Panca Mukti kabupaten Bengkulu Tengah - Perdana, Dionni Ditya (Universitas Teuku Umar, 2023)
Currently, social media accounts are not only owned personally but also have official accounts from companies or government agencies. Official social media from one agency is important both to establish communication to internally and externally as well as a forum for promotion and branding the image of the agency. The village government is currently not left behind to use social media, one of which is Panca Mukti Village, Bengkulu Tengah Regency, Bengkulu Province. In the service activities carried out to local village officials, it was recognized that it was true that the village already had social media accounts (one of which was Instagram), but was still constrained by the availability of human resources who managed it. In the counseling activities, material was given related to the urgency of using official social media, along with challenges and management strategies also accompanied by the practice of applying contemporary journalism in managing content on social media. From the discussion and counseling activities and training carried out, village officials have a stronger motivation in managing their social media and will reorganize related to the selection of resources that will be responsible for managing social media belonging to Panca Mukti Village, Bengkulu Utara Regency, Bengkulu Province.